Potential probiotic lactic acid bacteria isolated from fermented gilaburu and shalgam beverages - Akman, Perihan Kubra; Ozulku, Gorkem; Tornuk, Fatih; Yetim, Hasan (ELSEVIER, 2021)
Recently, there has been a growing interest for fermented food and drinks in the world for their possible health benefits. In this study, some lactic acid bacteria (LAB) strains were isolated from two different traditionally fermented Turkish beverages, gilaburu and shalgam and characterized in terms of their probiotic properties. According to obtained results, all the isolates had high resistance to low pH (2.5). Lactiplantibacillus pentosus strain XL963 was the most resistant bacteria to the acidity with a reducing rate of 1.05%. Meanwhile, Lactiplantibacillus. plantarum subsp. plantarum strain W2 was the most resistant isolate to bile salts while Limosilactobacillus fermentum strain Akhavan E3 was the most sensitive one with a reducing ratio of 7.33% at amount of 1.5% bile salts. All the isolates were able to deconjugate the bile salts at varying levels. The antimicrobial effect of the isolates on the test pathogens was also variable. Moreover, bacterial cells showed highly adhesive ability on the Caco-2 adenocarcinoma intestinal epithelial cells from ratio of 37%-88%. In conclusion, in this study, findings indicated that LAB strains isolated from traditional gilaburu and shalgam beverages exhibited high probiotic potential and could be used for designing different functional food products with great bioactive properties.
Keywords: Probiotic; Gilaburu; Shalgam; Caco-2 cells; Lactic acid bacteria; IN-VITRO; BIFIDOBACTERIUM STRAINS; LACTOBACILLUS STRAINS; ANTIBIOTIC-RESISTANCE; HYDROLASE ACTIVITY; FTIR SPECTROSCOPY; BILE-SALTS; IDENTIFICATION; SELECTION; SURVIVAL; Food Science & Technology